2018
DOI: 10.15405/epsbs.2018.02.120
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance: Scientific And Theoretical Discussions

Abstract: Each society faces a complicated problem of tolerance, which includes different spheres of social life. Manifestations of intolerant relations in behavior can be connected with social differentiation, social, economic and political conditions in the country, as well as with ethical, moral and cultural wealth in society.Analysis of a tolerance's concept and matter is represented in this article. It is known that demonstration of tolerance is determined by a social and cultural situation and therefore it is acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…The results of Set 6 with 14 measurements of six observables and two angles for L = 1 can be generalized theoretically for arbitrary L, as was found in photoproduction [2,11,12]. For each additional angular momentum, , each observable obtains two more Legendre coefficients, and therefore allows for two additional independent angular measurements.…”
Section: Set Included Partial Wavesmentioning
confidence: 90%
See 2 more Smart Citations
“…The results of Set 6 with 14 measurements of six observables and two angles for L = 1 can be generalized theoretically for arbitrary L, as was found in photoproduction [2,11,12]. For each additional angular momentum, , each observable obtains two more Legendre coefficients, and therefore allows for two additional independent angular measurements.…”
Section: Set Included Partial Wavesmentioning
confidence: 90%
“…which allows one to parameterize only three of the six transversity amplitudes. The form introduced by Omelaenko [11],…”
Section: Amplitudes Used In Pseudoscalar Meson Electroproduc-tionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a problem if one actually wants partial-wave amplitudes, as the undetermined phase may be different at each reconstructed energy and angle. In the analysis of pseudo-scalar photoproduction data, we do require multipole amplitudes in order to search for resonance content, and this has led to a renewed interest [7,8] in the properties of a truncated partial-wave analysis (TPWA), as has been described by Omelaenko [9] and Grushin [10].…”
Section: Introductionmentioning
confidence: 99%
“…At first sight this method seems to provide a direct connection between experimental data and multipole amplitudes. However, it has been demonstrated that possible ambiguities can only partially be resolved by high-quality experimental data alone [6][7][8]. All observables remain unchanged if at each energy and angular bin the reaction amplitudes are multiplied by an overall phase φ(W, θ).…”
Section: Introductionmentioning
confidence: 99%